"Government-Industry-University-Research- Promotion" Collaborative Innovation Mechanism Construction to Promote the Development of Agricultural Machinery Technology. Issue 17 (2018) - FuJun, Wen; Zhou, Yang; YingGang, Ou; XiangJun, Zou; JieLi, Duan
Abstract: In promoting the whole process mechanization of China's agriculture, agricultural machinery technology plays a key role.. This paper, based on the powerful " Government-Industry-University-Research- Promotion" collaborative innovation as to promote agricultural science and technology development. The paper analyzes the relationship between "Government-Industry-University-Research-Promotion " interaction, the main mode of cooperation at this stage. In promoting the development of agricultural machinery technology, there are five main bodies that do not form synergy, innovation incentive policies does not reach the designated position, the conversion rate of agricultural machinery science and technology is low, the result of scientific research is difficult to transform and so on. The article draws on the experience of "Government-Industry-University-Research- Promotion "form the United States, Japan, Israel countries. Put forward "under the government guidance, science and technology innovation as the drive, the enterprise as the main body, universities and research institutes as the technical support, project as the link "the coordination mechanism, Under this mechanism can establish "Government guide, Universities and research institutes led, enterprises led" three kinds of collaborative model. It provides reference for the innovation collaborative mechanism of agricultural machinery science and technology.